Policing Without Probity: the Discreditable Service of Superintendent John Robinson At Haverfordwest, 1851–61. (1st December 2020) - Hancock, Simon
This article examines the career of a police superintendent at Haverfordwest in Pembrokeshire between 1851 and 1861 as a case study of policing in a small town in the mid-nineteenth century. His ten-year service as chief of police witnessed his repeated breaching of the norms of probity and ethical behaviour, and his dishonesty revealed systemic weakness in maintaining police accountability. Personal and private interests compromised his public duties and this conflict led to his dismissal from the force.